The frequency of fingerprint patterns separated by ethnicity and sex in a general population from Sydney, Australia. (29th July 2019) - Walton, Andrew; Moret, Sebastien; Barash, Mark; Gunn, Peter
ABSTRACT: A total of 514 individuals from the Sydney area volunteered their fingerprint scans for analysis. The prints were classified using the eight main patterns of the National Crime Information Centre system. Additional information from the volunteers, including sex and ancestry, was documented. Using this information, the frequencies of each pattern for each biogeographical ancestry (BGA) group and sex were calculated. Trends showed that males and females have a difference in the frequency of plain arches; none of the other patterns showed clear differentiation. BGA trends showed that European and Middle Eastern groups had more similar frequencies for the less common patterns (plain arch, tented arch, radial loop, central pocket loop whorl and double loop whorl). Whereas for the common patterns of ulnar loop and plain whorl, European and South Asian groups were more similar in frequency.